The effectiveness of non-clozapine antipsychotics combined with electroconvulsive therapy versus clozapine combined with electroconvulsive therapy for treatment-resistant schizophrenia - Pichai Ittasakul,; Booncharoen P,; Tor PC, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
The study aimed to compare the effectiveness and safety of other atypical antipsychotics (non-clozapine) plus electroconvulsive therapy (ECT) (NC+ECT) versus clozapine plus ECT (C+ECT) for treating treatment-resistant schizophrenia (TRS). Data of 32 patients with TRS who was receiving ECT were analysed. We compared clinical characteristics, response to treatment [defined as an improvement of 40% in the Brief Psychotic Rating Scale (BPRS) psychotic symptom subscale from pretreatment scores], change of Mini-mental Status Exam (MMSE) scores, and other adverse effects between the NC+ECT group (N= 16) and C+ECT group (N =16). We found that the overall response rate was 65.6% (75.8% for the NC+ECT group and 56.3% for the C+ECT group, p=0.26). The overall BPRS score in both groups decreased significantly. The mean difference in total BPRS psychotic subscale score between pre-ECT and after last ECT was 10.4 + 5.8 (p<0.001) for the NC+ECT group and 6.6 + 7.3 (p = 0.002) for the C+ECT group. When comparing the NC+ECT group to the C+ECT group, the mean difference in total BPRS psychotic subscale score was not significant. (p = 0.104). The mean difference in MMSE score between pre-ECT and after the last ECT was -1.1 + 5.1 (p =0.45) for the NC+ECT group and 0.2 + 4.3 (p=0.855) for the C+ECT group. The change of MMSE score in the NC+ECT group was not significant different compare to the C+ECT group (p = 0.461). We concluded the combination of antipsychotics and ECT is an effective and safe treatment option for patients with TRS. Other NC+ECT groups’ efficacy may be comparable to that of clozapine plus ECT.